Design and Development of Satay Delivery Packaging Box - Marwee, Nur Nadiah; Masrol, Shaiful Rizal (Progress in Engineering Application and Technology, 2021)
Satay is one of Malaysia popular take away food with various type of packaging which have an issue of food freshness and sustainability. Therefore, this project has redesigned and developed a new packaging for Satay take away and delivery purpose. New redesigned of Satay packaging was developed using paper-based material through Quality Function Deployment (QFD) method through customer interview, Voice of Customers (VoC) and questionnaire to observed the consumer requirements and construct the House of Quality (HoQ) followed by design process via developing concepts, concepts selection, determining critical part, computer aided design (CAD) and produce a visual prototype. Food freshness, food temperature and sensory evaluation were also evaluated on the visual prototype compared to other types of packaging. The results shows that the new developed Satay delivery packaging is further complements to customer needs, recyclable and maintain the food freshness however need more in-depth study for mass application.